Stromal Cells Act as Guardians for Endothelial Progenitors by Reducing Their Immunogenicity After Co‐Transplantation. (23rd February 2017) - Souidi, Naima; Stolk, Meaghan; Rudeck, Juliane; Strunk, Dirk; Schallmoser, Katharina; Volk, Hans‐Dieter; Seifert, Martina
Abstract: Regeneration of injured tissues requires effective therapeutic strategies supporting vasculogenesis. The lack of instantly available autologous cell sources and immunogenicity of allogeneic endothelial (progenitor) cells limits clinical progress. Based on the immunosuppressive potency of mesenchymal stem/progenitor cells (MSCs), we investigated whether crosstalk between endothelial colony‐forming progenitor cells (ECFCs) and MSCs during vasculogenesis could lower allogeneic T cell responses against ECFCs allowing long‐term engraftment in vivo. Immunodeficient mice received subcutaneous grafts containing human ECFCs alone, or pairs of human ECFCs/MSCs from the same umbilical cord (UC) to study vasculogenesis in the presence of human leukocyte antigen (HLA)‐mismatched human peripheral blood mononuclear cells (PBMCs). In vitro, cell surface marker changes due to interferon gamma (IFNγ) stimulation during ECFC/MSC coculture were determined and further effects on allostimulated T cell proliferation and cytotoxic lysis were measured. IFNγ‐induced HLA‐DR expression on ECFCs and MSCs, but both cell types had significantly less HLA‐DR in cocultures. ECFC‐induced T cell proliferation was abolished after MSC coculture as a result of HLA‐DR downregulation and indolamin‐2, 3‐dioxygenase activation. Additionally, allospecific CD8 + T cell‐mediated lysis of ECFCs was reduced in cocultures. ECFC/MSC coapplication in immunodeficient mice not only promoted the generation of improved blood vessel architecture after 6 weeks, but also reduced intragraft immune cell infiltration and endothelial HLA‐DR expression following PBMC reconstitution. Crosstalk between UC‐derived ECFCs and MSCs after combined transplantation can lower the risk of ECFC rejection, thus enabling their coapplication for therapeutic vasculogenesis. Stem Cells 2017;35:1233–1245 Abstract : Interaction of endothelial colony forming cells and mesenchymal stromal/progenitor cells (MSCs) from umbilical cord under inflammatory conditions in vitro results in an inhibition of allogeneic T cell responses by reduced human leukocyte antigen‐DR expression on both cell types, and an indoleamine 2, 3‐dioxygenase‐dependent mechanism via MSCs. The coapplication in vivo in a humanized mouse model induces stable functional vascular networks and reduces the proportion of infiltrating human immune cells, thereby enhancing the general regenerative potential.